2015
DOI: 10.1177/0022343314558101
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating mediated talks

Abstract: Research on mediation has shown that mediation can be an effective conflict management tool to contain intrastate conflicts, prevent escalation of low intensity conflicts, and foster de-escalation. But can ripe moments for conflict prevention effectively be anticipated? This article argues that the short-term conflict history provides a good predictor of the probability of mediation onset in low-intensity conflicts. It builds on an expected utility theory of mediation and states that conflict intensity is a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Finally, mediation may be more likely in particular conflict contexts and could therefore be subject to a self-selection bias. Recent work has shown that mediation in civil wars is predicted by developments on the battlefield (Ruhe, 2015). In the supplementary files, I address this concern through the use of endogenous treatment models.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, mediation may be more likely in particular conflict contexts and could therefore be subject to a self-selection bias. Recent work has shown that mediation in civil wars is predicted by developments on the battlefield (Ruhe, 2015). In the supplementary files, I address this concern through the use of endogenous treatment models.…”
Section: Methodsmentioning
confidence: 99%
“…Two strive to predict different war outcomes, one using conflict dynamics suggested to be relevant by utility theory (Mason et al, 1999), the other using market data (Mitchener et al, 2015). More closely related to peace processes, Clayton and Gleditsch (2014) and Ruhe (2015) attempt to predict mediation onset, while Montoya and Tellez (2020) focus on public opinions on peace negotiations.…”
Section: Prediction and Explanations Of Peace Process Outcomesmentioning
confidence: 99%
“…Reiter, 2003), and the latter's historical and theoretical roots (Blainey, 1988;Clausewitz, 1980). Hence, several studies have used distance measures to explain or predict conflict management and outcome (Greig, 2015;Greig et al, 2018;Ruhe, 2015). We expand this literature and assess how well distance predicts agreement content.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, the notions of the mutually hurting stalemate and the ripe moment for seeking a settlement have become prominent: parties that are relatively equally balanced in their military capabilities and unable to achieve a decisive military victory become locked in a situation in which they must seek alternatives to a military strategy (Zartman 2001). This then creates a specific window of opportunity (Bapat 2005, Ruhe 2015.…”
Section: Theoretical Framework: Conflict Settlement In a Counter-terrmentioning
confidence: 99%